Correlation of the anthropometric parameters predictors of emerging risk for diabetes mellitus - Graciela Inés Ascar; Cintia Bassino; Cristina Beatriz Huespe; María Mercedes Hernández; Lourdes Aparicio (Centro Provincial de Información de Ciencias Médicas, 2020)
Introduction: There are risk anthropometric predictors parameters of suffering from diabetes mellitus that can be correlated, such as the body mass index, body fat percentage,   waist perimeter and visceral fat percentage.   Objective: To establish the potential risk of suffering from type2 diabetes mellitus by means of the correlation of indicators and anthropometric measures applicable to a local population.   Methods: An epidemiological, cross-sectional, observational and analytic study of 118 young individuals was carried out in the Catholic University of Córdoba, in Córdoba, Argentina, during the month of September, 2019, in which the FINnish Diabetes Risk Score was implemented, the body fat and visceral fat percentages were also taken as warning signs. In the statistical analysis of the quantitative and qualitative variables the average and the standard deviation were used as descriptive measures; also, the Shapiro-Wilks and Kolmogorow-Smirnov normality tests and the Spearman correlation test were implemented to prove the outlined statistical hypotheses.  Results: It was found that it was a low risk population and the correlation between the body mass index and the body fat that was adjusted was Y=1.18X+4.06; where Y was the body fat percentage and X the body mass index. To correlate the waist perimeter and the visceral fat percentage Y=0,21X-10,21 for men and Y=0,17X-7,84 for women were adjusted, where Y  was the visceral fat percentage and X the waist perimeter.  Conclusions: The knowledge of the population health condition leads to the training and assistance for the selfcare and to the acquisition of healthy habits that contribute to an adulthood with life quality.